All that glitters is not gold. (4th July 2019) - Mizumoto, Junki; Shimizu, Taro
Abstract : A 79‐year‐old Japanese woman presented with acute and diffuse abdominal pain, which turned out to be an unusual diagnosis. This article highlights a hint in physicians' diagnostic process, thereby avoiding the obstacles in making a correct diagnosis.